The Spanish Regional Policy: an assessment of economic incentives during the period 1988-2003 - Pedro B. Moyano; Guillermo Aleixandre; Olga Ogando (European Regional Science Association (ERSA), 2004)
Two main challenges influence the design of regional policies carried out by European, National and Regional policy makers. The first is the shift towards a knowledge-based economy, where enterprise competitiveness is increasingly linked to intangible assets. The second is the enlargement of the European Union that means important changes in the European Union marketplace and the possibilities of intervention in some less favoured regions. Until today, Regional Policy in many European Union countries has principally been founded on incentives for the creation of employment and investment in tangible assets. In this context, Spanish Regional Policy has been formulated, on the one hand, to achieve decentralisation of the entities responsible for its promotion and, on the other, to foster co-ordination and integration of Community, National and Autonomous Region interventions. Moreover, the design of this policy has taken into consideration the classical conflict between equity and efficiency. The objective of this paper is to assess the results and the gradual changes in regional incentive policy applied in Spain over the last 15 years and to identify the elements in which public intervention could be improved in order to adapt this policy to the demands laid out within the new environment previously defined. This assessment includes: firstly, a brief analysis of the evolution of public intervention; secondly, a study of the spatial distribution of the incentives over the period considered; and thirdly, a comparison of the economic performance of the different areas depending on the awards received. The analysis of this policy is based on a database comprising over 16 000 items referring to award decisions to applications for Regional Investment Grants (Law 50/1985 of 22 December 1985) gathered from the Official State Bulletin (Boletín Oficial del Estado, BOE) during the period 1988-2003. KEY WORDS: Spain, Regional policy, Regional incentive, Employment, Investment, Policy assessment
Keywords: 330; Spain; Regional policy; Regional incentive; Employment; Investment; Policy assessment